Analisis Lingkungan Kerja Fisik untuk Meningkatkan Kinerja Pegawai UPTD Balai Latihan Kerja di Dinas Tenaga Kerja dan Transmigrasi Kabupaten Karawang - Mustafa Kemal Pasha; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the work environment in the UPTD Balai Pelatihan Kerja and what are the problems in the work environment that affect the improvement of employee performance, and to find problems and solutions that can provide benefits as improvements for its employees. Through a qualitative descriptive method using case studies, field observations, and documents of research activity results. The results of this study indicate that an uncomfortable and ineffective work environment can cause a decrease in employee performance in the UPTD Balai Pelatihan Kerja Transmigration Karawang Regency, which has an impact as evidenced by the results of observations that there are several problems related to the work environment. Based on the results of the qualitative descriptive analysis, it can be concluded that by implementing new policies related to the work environment, employee performance can be improved, because a good and comfortable work environment will create working conditions that can provide employee motivation/enthusiasm to work. A good work environment is expected to increase employee performance which can provide benefits for both the organization and employees